Analisa Zat Warna Rhodamin B Pada Lipstik Gloss Dan Matte Yang Dijual Dikota Banda Aceh Dengan Metode Kromatografi Lapis Tipis - Azmalina Adriani; Rizki Andalia; Rinaldi Rinaldi; Nadhira Ulya (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Cosmetics are a very important need for women, one type of cosmetics that must be owned by women is lipstick. Lipstick is a lip color that has many colors. Rhodamine B is a synthetic dye that is prohibited for use in cosmetics and is declared a dangerous substance. This study aims to identify the presence or absence of Rhodamine B in gloss and matte sold in the city of Banda Aceh using the Thin Layer Chromatography (TLC) method. The population in this study was a sample of lipstick sold in the city of Banda Aceh with a sampling technique using a purposive sampling method. The criteria for lipstick taken from the gloss liquid, homogeneous, sharp smelling, red and purplish pink in color. Whereas matte has a semi-solid and smooth texture, has a purplish pink color and smells of lipstick in general and has a BPOM or not BPOM statement. Observations were made by looking at the stains under a 254 nm UV lamp. The results of this study were that of the eight samples, non-BPOM SS samples tested positive for Rhodamine B, with an Rf of 0.68 which is in line with the standard Rf value. In accordance with the requirements of the Regulation of the Food and Drug Supervisory Agency of the Republic of Indonesia Number 23 of 2019 concerning technical requirements for prohibited dyestuffs in cosmetics.